The Implementation of Group Discussion in Teaching Speaking to The Tenth Grade Students of SMA Negeri 4 Surabaya (RETAIN, 2013)
This study investigated how the implementation of Group Discussion in teaching Speaking in lights of the theories of group discussion. It sought the answers to the following questions: How does the teacher implement Group Discussion in her English lesson? What are the teacher’s reasons in using group discussion to teach speaking?. This study was limited to one teacher who used Group Discussion in teaching speaking in SMA Negeri 4 Surabaya. This study used descriptive qualitative as a research method. The data were taken from the results of field notes, and semi-structured interview. The data that were gotten were analyzed qualitatively. It was found that when the teacher used Group Discussion to teach Speaking at the class X-3 at SMA Negeri 4 Surabaya, her implementation was not similar with the theories of Group Discussion. The teacher added an activity in the implementation, but the students was quite active in the class. According to the teacher statement, group discussion is a good method, because it gives students some cognitive points. The teacher used narrative text as a topic of the discussion, the topic was not suitable to teach speaking. In conclusion, the implementation of group discussion in tenth grade students of Senior High School of SMAN 4 Surabaya was not similar with the theories of group discussion, but it still effective to develop students speaking ability. Key words : Speaking, Teaching Speaking, Group Discussion Abstrak Penelitian ini menginvestigasi bagaimana penerapan Group Discussion dalam mengajar speaking berkaitan dengan teori dari Group Discussion. Penelitian ini digunakan untuk menjawab pertanyaan berikut ini : Bagaimana gutu menerapkan Griup Discussion pada kegiatan mengajar bahasa inggris? Apa saja alasan guru menggunakan Gropu Discussion untuk mengajar speaking?. Penelitian ini dibatasi pada seorang guru yang menggunakan Group Discussion untuk mengajar speaking di SMA Negeri 4 Surabaya. Penelitian ini menggunakan deskriptif kualitatif sebagai metode penelitian. Data penelitian diambil dari hasil fieldnotes dan semi structured interview. Data yang sudah diperoleh akan dianalisis secara kualitatif. Ditemukan bahwa ketika guru menerapkan Group Discussion untuk mengajar speaking di kelas X3 SMA Negeri 4 Surabaya tidak sesuai dengan teori penerapan group discussion. Guru menambahkan kegiatan tambahan dalam penerapan Group Discussion, tetapi para murid cukup aktif ketika belajar di kelas. Berdasarkan keterangan dari Guru, Group Discussion itu metode yang bagus, karena memberi poin kognitif kepada siswa. Dalam penerapannya guru menggunakan narrative text sebagai topic untuk Group Discussion, topik tersebut tidak cocok untuk digunakan mengajar speaking. Disimpulkan bahwa penerapan Group Discussion pada kelas sepuluh di SMA Negeri 4 Surabaya tidak sesuai dengan teori dari Group Discussion, tetapi Group Discussion masih cukup efektiv untuk mengembangkn kemampuan speaking siswa.